VITAMIN C IN HEALTH AND DISEASE: VITAMINA C EN LA SALUD Y EN LA ENFERMEDAD - Castillo Velarde, Edwin Rolando (2019)
Vitamin C has been widely studied in medicine and although the importance of its deficiency with scurvy was recognized, the optimization of its use as a therapeutic resource has not been included in protocols or clinical practice guidelines. The pharmacokinetics and biology of vitamin C indicates the systemic effects it has, and based on it, research has been developed in recent years that supports its parenteral use in some diseases. The available evidence indicates that the benefit of its use does not extend to several diseases but to some such as cancer, whose preliminary report is promising, with adequate tolerability at high doses, but still needs to complete the prospective follow-up of the intervention.